The Link Between Financial Development and Poverty: A Spatial Analysis of Indonesia - Saputro, Nugroho; Nugroho, Linggar Ikhsan; Pamungkas, Putra; Pramusinta, Eka Dyah (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2024)
Research Originality: This research is original in its examination of the spatial influence of financial development on poverty in Indonesia.Research Objectives: This study investigates the impact of financial development on poverty reduction in Indonesia.Research Methods: This study employs a spatial econometric approach, analyzing data from 2016 to 2021. Key variables include credit-to-GDP ratio, third-party funding-to-GDP ratio, government spending, the human development index, and deposits-to-GDP ratio.Empirical Results: The findings reveal significant spatial dependence in poverty across Indonesian regions. The credit-to-GDP ratio did not significantly reduce poverty, whereas the third-party funding-to-GDP ratio showed a positive and significant effect on poverty reduction. Government spending, the human development index, and the deposits-to-GDP ratio contributed to poverty alleviation.Implications: These results suggest that Indonesia's financial sector development has not effectively reduced poverty. Policymakers should focus on targeted financial reforms, regional coordination, and improving socio-economic factors to enhance poverty reduction efforts.JEL Classification: C31, G21, I32, O18